IMC’s Development in Its Understanding of Evangelism and Chinese Christians’ Early Ministry in Self-Propagating the Gospel - Lin, Manhong (International review of mission, 2022)
Adequate research has been done on the relationship of evangelism to non-Christian religions, church mission, and culture. These topics have been studied and addressed when ecumenical organizations like the International Missionary Council (IMC) – now the Commission on World Mission and Evangelism (CWME) of the World Council of Churches – develop the theory of evangelism in their evangelizing enterprises. The China Continuation Committee was one of the founding members of the IMC in 1921, and thus proactively participated in the IMC’s mission. Chinese Christians inevitably encountered the same challenges in their early evangelizing attempts. This article examines Chinese Christians’ early efforts to self-propagate the gospel in the social environment of the first half of the 20th century in China. Chinese Christianity has demonstrated distinctive approaches to the above three key relationships, as Chinese Christians dedicate themselves to national salvation and liberation. It can even be said that in the first half of the 1900s, Chinese churches made more progress than other churches in the ecumenical world in such respects as indigenization and self-propagating ministry – even though some of the efforts were mingled with narrow-minded motives of converting Chinese people. It was not until the launch of the Three-Self Patriotic Movement that Chinese Christianity became an authentically autonomous Christian church, which has severed its ties with colonialism and started pursuing all-round self-reliance, including church evangelism. After analyzing the challenges that Chinese churches still face today in terms of evangelism, this article calls for Chinese Christianity to learn from IMC-CWME’s experience of evangelism for the further contextualization of Christianity in China. This aims at making the gospel proclamation carry more Chinese characteristics and eventually form an evangelism theology of Chinese Christianity. In this way, the outcome of the early efforts can be consolidated and the gospel message will better fit today’s Chinese context.